2019
DOI: 10.1097/md.0000000000017749
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis improving the outcome of an infant with epileptic encephalopathy with cytoplasmic FMRP interacting protein 2 mutation

Abstract: Rationale: Early infantile epileptic encephalopathy (EIEE) 65 was recently shown to be caused by the cytoplasmic FMRP interacting protein 2 (CYFIP2) mutation. To date, only 5 cases have been reported in two articles, and all the outcomes in all cases were poor.Patient concerns: In this study, we reported an 8-month-old girl with a 1 month-long history of seizures and developmental delay. Over 1 month later, she developed epileptic spasms in clusters with hypsarrhythmia on electroencephalography. Diagnosis:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…In conclusion, our study suggests that L5‐specific prefrontal dysfunction, especially hyperexcitability, underlies both the pathophysiology and the lithium‐mediated amelioration of neurobehavioral phenotypes in adult Cyfip2 +/− mice. Beyond CYFIP2 haploinsufficiency, these results, if supported by follow‐up studies, might also be implicated in ID and epilepsy of patients with CYFIP2 missense variants, 7–10 because both types of CYFIP2 variants are expected to induce common molecular changes, such as aberrant actin polymerization 18,60 . Prefrontal L5 neurons might be more vulnerable to these CYFIP2‐dependent changes in the maintenance of their normal function.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In conclusion, our study suggests that L5‐specific prefrontal dysfunction, especially hyperexcitability, underlies both the pathophysiology and the lithium‐mediated amelioration of neurobehavioral phenotypes in adult Cyfip2 +/− mice. Beyond CYFIP2 haploinsufficiency, these results, if supported by follow‐up studies, might also be implicated in ID and epilepsy of patients with CYFIP2 missense variants, 7–10 because both types of CYFIP2 variants are expected to induce common molecular changes, such as aberrant actin polymerization 18,60 . Prefrontal L5 neurons might be more vulnerable to these CYFIP2‐dependent changes in the maintenance of their normal function.…”
Section: Discussionmentioning
confidence: 82%
“…Whether the age‐specific differences in the regulation of potassium channel genes in the PFC and possibly other brain regions are involved in the age‐specific phenotypes of Cyfip2 +/− mice requires further investigation. More importantly, patients with CYFIP2 missense variants show early‐onset clinical symptoms 7–10 . Therefore, our results for adult Cyfip2 +/− mice should be interpreted with caution and might not translate directly to human CYFIP2 ‐associated brain disorders.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Large chromosomal deletions harboring CYFIP2 have been identified in patients with developmental delay, ID, and seizures (Spranger et al, 2000;Lee et al, 2016). Moreover, recent whole-exome and whole-genome sequencing studies have identified de novo CYFIP2 variants in patients with developmental delay, ID, and early-onset epileptic encephalopathy (Nakashima et al, 2018;Peng et al, 2018;Lee et al, 2019b;Zhong et al, 2019;Zweier et al, 2019).…”
Section: Introductionmentioning
confidence: 99%